Tracts of high or low sequence divergence in the mouse major histocompatibility complex. - Steinmetz, M (1984)
The K, I and S regions of the mouse major histocompatibility complex (MHC) are composed of long tracts of DNA which differ in sequence divergence. A correlation exists between the location of an MHC gene in a variable or conserved chromosomal tract and the degree of polymorphism and diversity of the proteins encoded by its alleles. Variable tracts appear to be the result of mechanisms which mutate certain coding and non-coding sequences to the same extent and selective pressures operating on the genes.